2011
DOI: 10.1038/jhg.2011.131
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant microduplications of MECP2 and ATRX in male patients with severe mental retardation

Abstract: the Japanese Mental Retardation Consortium 8Investigations of chromosomal rearrangements in patients with mental retardation (MR) are particularly informative in the search for genes involved in MR. Here we report a family with concomitant duplications of methyl CpG binding protein 2 (MECP2) at Xq28 and ATRX (the causative gene for X-linked alpha thalassemia/mental retardation) at Xq21.1 detected by array-comparative genomic hybridization. The alterations were observed in a 25-year-old man who inherited them f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…However, the activity of ATRX probably involves remodeling of heterochromatin structure through the helicase activity of this protein as some mutations in ATRX that cause ATRX syndrome have recently been shown to disrupt its ATP hydrolysis activity 128 . Interestingly, a recent study identified a patient with severe intellectual disability who carries duplication of both MeCP2 and ATRX, suggesting a possible functional link between these two proteins in regulating cognition 129 .…”
Section: Biological Importance Of Methylation Dynamicsmentioning
confidence: 99%
“…However, the activity of ATRX probably involves remodeling of heterochromatin structure through the helicase activity of this protein as some mutations in ATRX that cause ATRX syndrome have recently been shown to disrupt its ATP hydrolysis activity 128 . Interestingly, a recent study identified a patient with severe intellectual disability who carries duplication of both MeCP2 and ATRX, suggesting a possible functional link between these two proteins in regulating cognition 129 .…”
Section: Biological Importance Of Methylation Dynamicsmentioning
confidence: 99%
“…The concomitant microduplications of MECP2 and ATRX in male patients with severe ID in one family [Honda et al, ] were not quite different than those usually found in patients with MECP2 duplication, except that the proband was found to have cerebellar atrophy, with many of the clinical features common to both duplication syndromes. These patients did not show some characteristics associated with duplications of ATRX, such as short stature or mid‐face hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Such mutations are commonly distinguished from low-level gains/losses using a direct threshold of array data. However, the threshold value often differs greatly, ranging from a log 2 ratio of +/−0.4 for some studies [46,47] to as high as +/−1.0 for others [48,49]. The criteria we used to detect deletions were based on the aCGH patterns obtained from our mutant versus wild type hybridizations.…”
Section: Methodsmentioning
confidence: 99%